ISLAM MOZAIK PERADABAN ISLAM - Suniati; Maksum; Muhammad Hori; M. Ilham Fikron; Ahmad Salim Ulul Albab (PT. Hasba Edukasi Mandiri, 2025)
Islamic civilization represents a complex and dynamic mosaic shaped by the interaction of religious doctrine, intellectual traditions, socio-political institutions, and diverse cultural expressions. This article aims to analyze Islam as a civilizational mosaic by examining its historical evolution, epistemological foundations, and contributions to global civilization. Employing a qualitative library research method, this study draws upon classical and contemporary scholarly works. The findings reveal that Islamic civilization developed through a process of cultural integration and intellectual exchange, enabling it to make significant contributions in science, philosophy, art, governance, and ethics. Understanding Islam as a mosaic civilization provides a more comprehensive perspective on its pluralistic character and reinforces its relevance in addressing contemporary global challenges.